Mast Cell Association In Hemangiomas and Arteriovenous Vascular Malformations. - Pawane, Pravin (Annals of Pathology and Laboratory Medicine, 2015)
Background: Vascular anomalies, classified as hemangiomas and arteriovenous Â Â malformations (AVMs), were analyzed for the presence of mast cells. Hemangiomas in the proliferative phase contained large numbers of mast cells (53.12 Â± 27.83 cells/mm2) Â in comparison with hemangiomas in the involuting phase (11.43 Â± 7.9 cells/mm2), and AVM (25.31 Â± 27.3 cells/mm2). Considering the fact that hemangiomas are characterized by endothelial proliferation and increased numbers of mast cells, these data raise the possibility that mast cells may have an important role in the formation and/or maintenance of these lesions. Aim: This study aimed at evaluation of presence of mast cells in hemangiomas proliferating, involuting ones and AVMs. Methods: A total of 120 cases of benign vascular lesions were retrieved from 12 years period. A total of 94 cases, where complete clinical details and representative paraffin sections were available, were included in this study. Hematoxylin and eosin (H and E) stain and Mast cell density in all lesions was calculated from toluidine blue stained sections. Results: Â Mean mast cell density was significantly higher in proliferating hemangiomas (53.12 Â± 27.83 cells/mm2) compared to involuting hemangiomas (11.43 Â± 7.9 cells/mm2) and AVM (25.31 Â± 27.3 cells/mm2) Conclusions: The significantly higher mast cell density seen in proliferating hemangiomas compared with involuting ones, seem to suggest that mast cells play an important role in the natural history of these lesions.